2004
DOI: 10.1038/sj.bjc.6601399
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene-expression profiles associated with gastric adenoma

Abstract: Gastric adenomas may eventually progress to adenocarcinomas at varying rates. The purpose of the present study was to identify gene-expression profiles linked to the heterogeneous nature of gastric adenoma as compared to adenocarcinoma. Suppression subtractive hybridisation analysis was performed to extract relevant genes from two cases of low-and high-grade gastric adenomas. The identified genes were quantified by RT -PCR in 14 low-grade adenoma, nine high-grade adenoma and nine adenocarcinoma samples, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…The removal of category 3 lesions (low-grade dysplasia), based on that classifi cation, is not necessary, whereas the removal of category 4 lesions (high-grade dysplasia and intramucosal cancer) is obligatory, because more than 80% of high-grade adenomas progress to adenocarcinomas [7]. However, there are frequently cases that do not easily fi t into the diagnostic categories; 15%-30% of low-grade adenomas progress to high-grade adenomas or adenocarcinomas [8,9]. Therefore, it is diffi cult for clinicians to determine which low-grade adenomas will progress.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of category 3 lesions (low-grade dysplasia), based on that classifi cation, is not necessary, whereas the removal of category 4 lesions (high-grade dysplasia and intramucosal cancer) is obligatory, because more than 80% of high-grade adenomas progress to adenocarcinomas [7]. However, there are frequently cases that do not easily fi t into the diagnostic categories; 15%-30% of low-grade adenomas progress to high-grade adenomas or adenocarcinomas [8,9]. Therefore, it is diffi cult for clinicians to determine which low-grade adenomas will progress.…”
Section: Introductionmentioning
confidence: 99%
“…OLFM4 protein expression has been observed in the oesophagus, stomach, small intestine and colon using immunohistochemistry [11]. In the recent years, increasing evidence indicates that OLFM4 is highly expressed in several types of tumors such as gastric [5,[12][13][14][15], pancreas [16], lung [16], breast [16] and colon [5,16,17] and is barely detectable in other tumors as well as in healthy tissues. OLFM4 expression is even related to tumor differentiation and progression and clinical course of diseases.…”
mentioning
confidence: 99%
“…A number of previous studies have suggested that low-grade dysplasia (LGD) progresses to HGD [34][35][36][37], and that HGD becomes invasive GC within several months [38][39][40][41][42][43]. In 20-40 % of cases, diagnostic discrepancy between dysplasia evident at biopsy and GC observed in the resection specimen has been reported [34,37,44].…”
Section: Discussionmentioning
confidence: 99%